HUBUNGAN ANTARA STATUS BEKERJA IBU DENGAN PENCAPAIAN TUMBUH KEMBANG ANAK USIA BATITA DI KELURAHAN MAASING KECAMATAN TUMINTING KOTA MANADO - Jeane Utina; Sofina Palamani; Esther Tamunu (POLTEKKES KEMENKES MANADO, 2012)
Child’s growth and development covers two events that are different but inter related and difficult toseperate.Which have an impact on physical growth and development related to the maturation of organfunction.Working mother’s often have an impact on children are able to self contained and selfconfidence and social good, negatif impact is the mother becomes less time with children, attentionlimited affection for the child because the mother is a long time outside the home.Type of recearch isobservational analityc with cross sectional design subjects with mother of childrden aged 1-3 years with asample size of 100 people. According to the education level of respondents in this study known to themajority of 70% of high school, working status of mothers known to 47% of work consists of 31,3% ofcivil servants and of private employees , 38,4% of traders, fisher 10%, servis industri 8,1%, traived12,2%. This study found a toddler with a good nutritional status and malnutrition 91%. Assessment of thedevelopment of 'appropriate' 57%, 37% 'dubious', 7% deviant. This study has a cross-tab the status ofworking mothers with toddlers nutritional status, weight / age: malnutrition 4 people, on working mothersand less nutritional status of 3 people, . The results of statistical tests with Fischer exacte showed nodifference p = 0,474 (p > 0.05). Crosstab status working mothers with toddlers nutritional status,height/age: short 19 people, in the mother works, the short 14 people in women who do not work. Theresults of the Fisher exact statistical test showed no differences in p = 0,037 (p < 0.05). Crosstab statusworking mothers with toddlers nutritional status, body weight/height on working mothers: three skinnypeople, In the mother does not work: skinny 3 people, Fisher exact statistical test results of no differencep = 0,731(p > 0,05), Crosstab with the status of working mothers working mothers on children'sdevelopment: the deviation 5, in the mother works; in the mother does not work:2 people irregularities. Fisher exact statistical test results showed no difference in p= 0, 317(p > 0,05).